Khūmư̄ kānčhattham lān kīlā ʻanēkprasong radap chumchon-tambon (Kō̜ng Phang Mư̄ang Chapho̜, Krom Yōthāthikān læ Phang Mư̄ang, Krasūang Mahātthai, 2006)
On the construction of multi-purpose sport stadiums in local communities of Thailand.